تأثير بُعدي المشاركة وتحديد الهويّة في المجتمعات الافتراضية على العلامة التجارية (دراسة ميدانيّة في شركتيّ الاتّصالات Syriatel و MTN) - غدير باسم; قنجراوي صابرين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Brand communities are ideal tools for e-commerce activities, especially e-marketing activities. The focus on virtual communities and their concepts can clearly lead to significant financial returns through the production of information systems that attract and retain users, effectively empowering user interactions and managing content produced and managed by the user. This provides many benefits and opportunities for brand organizations, through which they can improve customer service and relationships, easily disseminate information, and can also take the role of the public forum to share knowledge, learn and collaborate, as well as to form communities of common interests. On the other hand, virtual communities can be used to disseminate negative information about a brand, which may harm its reputation and lead to a loss in its customers. This impact of virtual communities should be taken by organizations, and how they should be used to their advantage, as well as reducing their potential risks. The objective of the research is to determine the impact of both post-participation and post-identification in virtual communities on the brand in Syriatel and MTN. A Google questionnaire was designed and published on the Facebook virtual platform. The main findings of the study were that the virtual communities under study achieved the possibility of participation and communication, but did not provide the link between the identity of the individual and the identity of the virtual community of the brand, and the process of building a mental image and loyalty and moving a word from the two trademarks under study have a significant impact on the brand. تعدّ المجتمعات الافتراضيّة للعلامات التّجارية أدوات مثاليّة لأنشطة التّجارة الالكترونيّة، وخاصّة أنشطة التّسويق الإلكتروني. كما أنّ التّركيز على المجتمعات الافتراضيّة ومفاهيمها يمكن أن يؤدّي بوضوح إلى عوائد ماليّة كبيرة من خلال إنتاج نظم معلومات تعمل على جذب المستخدمين والحفاظ عليهم، عبر التّمكين الفعّال لتفاعلات المستخدمين وإدارة المحتوى الذي ينتجه المستخدم وتقدّمه الإدارة. وبهذا توفر منافع وفرص عديدة للمنظمّات ذات العلامة التّجارية، فمن خلالها تستطيع تحسين خدمة العميل وعلاقاتها معه، ونشر المعلومات بسهولة، وأيضاً يمكنها أن تأخذ دور المنتدى العام لمشاركة المعرفة، والتّعلم، والتّعاون، وأيضاً تشكيل مجتمعات المصالح المشتركة. ومن ناحية أخرى، يمكن للمجتمعات الافتراضيّة أن تُستخدم لنشر معلومات سلبيّة عن العلامة التّجارية، والتي قد تضرّ بسمعتها، وتؤدي لخسارة في عملائها. هذا التّأثير للمجتمعات الافتراضيّة يجب أن تأخذه المنظّمات بعين الاعتبار، وأن تحدد كيفيّة استخدام هذه المجتمعات لمصلحتها، وكذلك تخفيض مخاطرها المحتملة. هدف البحث إلى تحديد تأثير كل من بعد المشاركة وبعد تحديد الهوية في المجتمعات الافتراضية على العلامة التجارية في شركتيّ الاتصالات السوريتين Syriatel و MTN. وتمّ تصميم استبيان الكتروني ونشره على منصة فيس بوك الافتراضية. وتمثلت أهم نتائج البحث بأن المجتمعات الافتراضية محل الدراسة تحقق إمكانية المشاركة والتواصل لكنها لا توفر حالة الارتباط بين هوية الفرد وهوية المجتمع الافتراضي للعلامة التجارية، كما أن عملية بناء الصورة الذهنية والولاء وتحريك كلمة منقولة عن العلامتين التجاريتين محل الدراسة ذات تأثير كبير على العلامة التجارية.